The Role of Parents in the Growth and Development of Early Childhood by Identifying Interests and Talents - Asti Nur Hadianti (STIT Attaqwa, 2025)
Children are born with different potentials. Mothers and fathers are the primary caregivers of children, and they are responsible for helping children develop their potential. In the golden age, children grow very rapidly at an early age. Every situation that encourages them to develop is very useful for their future growth role. This paper aims to describe the role of parents in the development of children at an early age or during the golden age. The methodology used in this paper is a literature study where data collection is carried out by collecting previous literature on the data needed by the author such as books, journals, and other sources. This study concluded that the role of parents is very important in developing children's potential. Parents can help develop children's potential in several ways. First, parents can start by identifying the child's interests and talents. Furthermore, parents can find and grow the child's potential by providing the right stimulus such as appreciating, praising, and teaching children to be creative according to their potential.